Another de novo mutation in the SOD1 gene: the first Turkish patient with SOD1-His47Arg, a case report - Bayraktar, Elif; Çiftçi, Vildan; Uysal, Hilmi; Başak, A. Nazlı (Frontiers in Genetics, 2023)
Amyotrophic lateral sclerosis (ALS) is a fatal, progressive neurodegenerative disease of motor neurons. Most ALS cases are considered sporadic due to the presence of a combination of environmental and complex genetic risk factors, while approximately 10% of cases have a family history. Pathogenic variants in the SOD1 gene are the second most frequent causative factor of genetics-based ALS worldwide, after C9ORF72 hexanucleotide repeat expansion. The De novo occurrence of pathogenic mutations in ALS-associated genes and its effect on disease progression have been studied previously, especially in the FUS gene. Recent studies have shown that a very small portion of SOD1 cases occurred de novo. Here, we present the first de novo case of the SOD1 His47Arg mutation in a young female patient with mild symptoms and, currently, a slow progression for 7 years.